Celastrol protects mouse retinas from bright light-induced degeneration through inhibition of oxidative stress and inflammation. Issue 1 (December 2016) - Bian, Minjuan; Du, Xiaoye; Cui, Jingang; Wang, Peiwei; Wang, Wenjian; Zhu, Weiliang; Zhang, Teng; Chen, Yu
Abstract Background Photoreceptor death leads to vision impairment in several retinal degenerative disorders. Therapies protecting photoreceptor from degeneration remain to be developed. Anti-inflammation, anti-oxidative stress, and neuroprotective effects of celastrol have been demonstrated in a variety of disease models. The current study aimed to investigate the photoreceptor protective effect of celastrol. Methods Bright light-induced retinal degeneration in BALB/c mice was used, and morphological, functional, and molecular changes of retina were evaluated in the absence and presence of celastrol treatment. Results Significant morphological and functional protection was observed as a result of celastrol treatment in bright light-exposed BALB/c mice. Celastrol treatment resulted in suppression of cell death in photoreceptor cells, alleviation of oxidative stress in the retinal pigment epithelium and photoreceptors, downregulation of retinal expression of proinflammatory genes, and suppression of microglia activation and gliosis in the retina. Additionally, leukostasis was found to be induced in the retinal vasculature in light-exposed BALB/c mice, which was significantly attenuated by celastrol treatment. In vitro, celastrol attenuated all-trans -retinal-induced oxidative stress in cultured APRE19 cells. Moreover, celastrol treatment significantly suppressed lipopolysaccharides-stimulated expression of proinflammatory genes in both APRE19 and RAW264.7 cells. Conclusions The results demonstrated for the first time that celastrol prevents against light-induced retinal degeneration through inhibition of retinal oxidative stress and inflammation.